El rastre de la "Historia destructionis Troiae" de Guido delle Colonne en la versió catalana de la Histoire ancienne jusqu’à César del ms. 352 de la Biblioteca de Catalunya - Perujo Melgar, Joan M. (2017)
The paper analyses the influence of Guido delle Colonne’s Historia destructionis Troiae (HT) on one of the two extant Catalonian translations of Histoire ancienne jusqu’à César (HAC), as it appears in manuscript 352 of Biblioteca de Catalunya. The analysis focuses mainly on the episodes related to the adventures of Jason, the Argonaut, in the Quest for the Golden Fleece, narrated in fragments inserted in that Catalonian translation of HAC, which are directly derived from delle Colonne’s work. The analysis makes it possible to ascertain that the Catalonian translator/compiler of this version of HAC used the Latin text of HT rather than Jaume Conesa’s Catalonian translation despite the fact that he combined it with some details from the Catalonian translation of Seneca’s Medea, a work also included in this Catalonian version of the compendium history. The narrative, based on the Latin text of HT, which is an innovation with regard to HAC, was therefore structured in a curious way by including elements taken from that tragedy by Seneca (references to Orpheus, allusion to the dismembering of Medea’s younger brother, etc.). The analysis also focuses on translation errors and sheds light on some specific, misleading elements of this version (for example, the fact that a dwarf attends Medea in her chamber) that might have been thought to be taken from an unknown source. As the Trojan section of ms. 352 has not been published before (except for some small fragments), the edition of the episodes of the Trojan history studied here has been included as an appendix.
Keywords: Colonne, Guido delle